Narrative structures and platform influences in digital prose: A study of Gérard Genette’s structural narratology and Marie-Laure Ryan’s transmedial narratology - Wulandari, Sovia; Fitriah, Siti; Triandana, Anggi; Putri, Aprilia Kartika; Rahariyoso, Dwi (Universitas Ahmad Dahlan, 2026)
The main aim of this research is to elaborate the narrative structure of digital prose across various online platforms and examine how digital media characteristics influence storytelling forms. A qualitative approach and the integration of Gérard Genette’s structural narratology with Marie-Laure Ryan’s transmedial narratology are applied. The object of this research is the selected texts from Wattpad, Webtoon, Fizzo, and Karyakarsa. The findings of this research show that digital prose tends to apply linear yet accelerated and fragmented narrative structures, characterized by dominant internal focalization and homodiegetic narration to enhance reader engagement. Furthermore, each platform shapes narrative configuration differently. For example, Webtoon emphasizes multimodal and spatialized storytelling, Wattpad facilitates participatory, community-driven narrative; third, Fizzo promotes compressed, fast-paced storytelling; and fourth, Karyakarsa integrates a narrative production with social and economic interaction. These results reveal that digital prose is not simply an extension of printed literature, but it is a platform-dependent narrative form which is shaped by the interaction between textual strategies (narratology structure) and technological affordances (transmedial narratology). This study contributes to digital narratology by highlighting how platform features actively reconfigure narrative structures and reader–text relationships in contemporary storytelling.